Autonomous grass cutter part II - Chew, Jia He (Nanyang Technological University, 2020)
In this project, the main objective is to understand the capabilities of existing products and fabricate an autonomous grass cutter which is portable, durable, and easy to maintain. It also aims to be designed as a cordless electric grass cutter. This project is started with the research on the current method used in Singapore, identify the problems and conduct market analysis on some existing products that had been selling in the market. The prototype was then fabricated into the real product size and programmed to be autonomous by using Arduino microcontroller and its software. The prototype had been fabricated successfully with some functionalities, such as operate on slopes and obstacle detection. However, there are improvements could be made in the future before it becomes a real product. This project has excellent potential to benefits not only the government but also to home users as well.